Working to overcome the global impact of neglected tropical diseases : first WHO report on neglected tropical diseases (WTO GenevaCH, 2010)
Highlights a number of remaining challenges for the control and even elimination of tropical diseases. Sets out the evidence needed to achieve control. Makes the case for doing more, as an international community, to relieve misery, among people who would otherwise suffer in silence.
Keywords: TROPICAL DISEASES